Emulsifying agents applied to the stabilization of o/w emulsions in order to improve heavy oil transportation through pipelines: A bibliometric study (Research, Society and Development, 2021)
The growing demand for energy associated with the progressive decline in conventional oil reserves (extra-light oil, levels and medium) have encouraged the exploration of heavy and extra-heavy oils fields. However, due to several intrinsic characteristics of these oils, exploring, transporting and refining them are still challenges to be overcome. Thus, the present work aimed to present a bibliometric review on the main emulsifying agents that have been used in the stabilization of heavy oil in water (O/W) emulsions, in order to improve the flow of these oils under surface conditions (flow in pipelines). The research was carried out using the Science Direct, One Petro and Web of Science platforms, inserting the following keywords: Heavy crude oil; Oil-in-water emulsion; Stability; Pipeline transportation. The time span was limited to 10 years (2011-2020) and, subsequently, the inclusion/exclusion criteria were applied, in order to refine the research. As a result, a total of 18 scientific articles were obtained. Among the countries that were most interested in the topic, we can highlight India, Norway, Mexico, China, the United States and Iran. In relation to the emulsifiers most used in stabilizing O/W emulsions, surfactants and solid particles were the most cited. Although nonionic surfactants have been identified as the most efficient, more detailed studies are still needed to understand the mechanism of these agents, as well as to evaluate the ability of these compounds to stabilize O/W emulsions under surface flow conditions.